METHODOLOGY OF USING MODERN GRAPHICS PROGRAMS IN TEACHING ENGINEERING GRAPHICS - Qutbiddinov Hikmatillo Qudratillo og'li (American Journals, 2024)
This article reflects the role of computer graphics in the teaching of engineering graphics and an improved method of teaching modern automated design software.
Keywords: CAD, natural processing, artificial processing, computer graphics, engineering graphics.